Inventories in National Economies A Cross-Country Analysis of Macroeconomic Data - Chikán, Attila; Kovács, Erzsébet; Matyusz, Zsolt; Sass, Magdolna; Vakhal, Péter (Springer London : Imprint: Springer, 2018)
XIV, 314 p. 173 illus., 39 illus. in color.